Contemporary theories about international relations - Fernandes de Oliveira, Marcelo (FCL-UNESP Laboratório Editorial, 2007)
This paper has its main objective to analyse two contemporary theories in the área of international relations: the liberal intergovernmentalist, identified as the global paradifm, and the jodo de Dois Níveis, which refers to the interation between the local interlocutors and the international negotiatiors in cooperative processes between States. Both of them are relevant to the understanding of the present international context as well as to the analysis of how the externai politics of each State is built in general, and, in particular, the Brazilian one, mainly in what concerns the processesof regional integration that his country is negotiating, i.e., The Southern Common market and ALCA.